Comparison of two instruments for hypertension self‐care assessments among older adults from China - Qiao Zhao; Yujie Guo; Lipei Gu; Lei Yang (Wiley, 2023)
Abstract Aim To test and compare the Self‐Care of Hypertension Inventory (SC‐HI) and Hypertension Self‐Care Profile (HBP SCP) among older patients with hypertension in China. Design A cross‐sectional observational study. Methods A convenience sampling of 220 older adults (120 male patients and 100 female patients) with hypertension and a mean age of 73.74 years was surveyed using the Chinese version of SC‐HI, the Chinese version of HBP SCP and the Chinese version of Exercise of Self‐Care Agency Scale (ESCA) during July‐September 2019. Psychometric analyses and Receiver Operating Characteristic curve analyses were performed on the collected data. Results The Cronbach's α of SC‐HI and HBP SCP was 0.858 and 0.953, respectively. The Pearson's coefficients between the SC‐HI total score and the ESCA total score, the HBP SCP total score and the ESCA total score were 0.494 and 0.700, respectively. The satisfactory sensitivity, specificity, cut‐off point and Area under the curve of SC‐HI were 0.8292, 0.5495, 120.5 and 0.754, respectively. As for HBP SCP, the values were 0.7907, 0.7582, 169.5 and 0.838, respectively. There was no significant difference between these two scales. Each has its own characteristics. However, the HBP SCP is more precise and effective for measuring self‐care ability in older patients.